The thirteen ghosts - Stilton, Geronimo; Bigarella, Ivan , 1984; Campioni, Giorgio; Clement, Emily (New York : Scholastic Inc., 2010)
Creepella von Cacklefur and her niece, Shivereen, visit scary Squeakspeare Mansion. There they meet Bobby Squeakspeare, a descendent of the famouse writer, William Squeakspeare. Will the spooky rooms and ghosts they find inside the mansion be friendly--or frightening?
Keywords: Stilton, Geronimo -- Juvenile fiction; Mice -- Juvenile fiction; Ghost stories; Haunted houses -- Juvenile fiction; Stilton, Geronimo -- Fiction; Mice -- Fiction; Ghost -- Fiction; Haunted houses -- Fiction